Comprehensive Review of Health Workers’ Impact on Precision Medicine - Alsharhoof, Saleh Mahdi A; Hassan, Hassan Abdullah; Almajhed, Alia Ibrahem Abdulla; Algannam, Sajdh Ali; Alanazi, Reem Obaid Mana; Alanazi, Abeer Obaid Mana; Alminhaly, Eidah Mohameed Saleem; Al Ajmi, Fahad Abdullah F; Al Abbas, Saleh Hadi Saud; ALYami, Abdullah Mahdi (Journal of Ecohumanism, 2024)
Precision medicine is the new frontier in health management since it involves the development of management at the molecular level of the individual patient by considering his/her genomic, environmental, and lifestyle characteristics. The special contribution of these scientific achievements to the reality of current and future healthcare delivery systems cannot be overemphasized; better said, the scrip-swinging part played by health workers worldwide in actualizing these discoveries need not be overemphasized. This comprehensive review explores the multiple roles of health professionals, especially clinicians, nurses, genetic counselors, and laboratory personnel in precision medicine. It situates the study with other research works, highlights the major knowledge gaps, and discusses challenges and opportunities for target health workers. In addition, the study presents actionable suggestions for improving their inclusion within the precision medicine paradigm while maintaining equal access to and effectiveness of service delivery.